Multimodal Preoperative Localization Improves Outcomes in Reoperative Parathyroidectomy: A 25-Year Surgical Experience. Issue 9 (September 2019) - Patel, Snehal G.; Saunders, Neil D.; Jamshed, Salman; Weber, Collin J.; Sharma, Jyotirmay
Reoperative parathyroid surgery (REOPS) is often associated with lower cure rates and greater risk of nerve injury and hypoparathyroidism. The aim of this study was to evaluate cure rates, pathology, complications, and the efficacy of preoperative localization in patients requiring REOPS. Between 1992 and 2017, 2491 consecutive patients underwent parathyroidectomy for primary hyperparathyroidism. With Institutional Review Board approval, our prospectively collected parathyroidectomy outcomes database was queried for operative findings, outcomes, pathology, and localization methodology. Three hundred forty-six patients had REOPS (111 men/32% and 235 women/68%), with an overall cure rate of 91 per cent and a mean follow-up of 1.9 ± 0.7 years. The average preoperative serum calcium and parathyroid hormone were 11 ± 1 mg/dL and 373 ± 796 pg/mL, respectively. Normalization of intraoperative parathyroid hormone occurred in 248 patients and it was predictive of cure in 98.8 per cent of patients. A single adenoma was resected in 253 patients (75%), and the superior gland location was most common at 57 per cent. Ectopic glands were identified in only 33 patients. When preoperative imaging localized a lesion, a tumor was identified in that location in 75.4 per cent of sestamibi or SPECT/CTscans, 57.8 per cent of CT, 61.2 per cent of MRI, and 46.2 per cent of US. When at least two imaging modalities were concordant, sensitivity improved to 91.6 per cent ( P < 0.001). Complication rates of permanent hypoparathy-roidism and recurrent nerve palsy occurred in 0.03 per cent of patients. REOP for recurrent or persistent primary hyperparathyroidism has a cure rate of 91 per cent. Most missed parathyroid tumors are in the neck, and multimodal imaging improves preoperative localization and success.